Association of Triple Therapy With Improvement in Cholesterol Profiles Over Two‐Year Followup in the Treatment of Early Aggressive Rheumatoid Arthritis Trial. Issue 3 (March 2016) - Charles‐Schoeman, Christina; Wang, Xiaoyan; Lee, Yuen Yin; Shahbazian, Ani; Navarro‐Millán, Iris; Yang, Shuo; Chen, Lang; Cofield, Stacey S.; Moreland, Larry W.; O'Dell, James; Bathon, Joan M.; Paulus, Harold; et al.
Abstract : Objective: To evaluate long‐term changes in cholesterol levels in patients with early rheumatoid arthritis (RA) who were randomized to begin treatment with methotrexate (MTX) monotherapy, MTX plus etanercept, or triple therapy (MTX plus sulfasalazine plus hydroxychloroquine) in the Treatment of Early Aggressive Rheumatoid Arthritis (TEAR) trial. Methods: Levels of total cholesterol, low‐density lipoprotein (LDL) cholesterol, and high‐density lipoprotein (HDL) cholesterol were analyzed in 416 patients participating in the TEAR trial, during 102 weeks of followup. Associations of cholesterol changes with disease activity and drug treatment were evaluated using repeated‐measures analysis with mixed‐effect linear models to model within‐subject covariance over time. Results: Mixed‐effect models controlling for traditional cardiovascular (CV) risk factors, TEAR treatment, and baseline prednisone and statin use demonstrated significant inverse associations of RA disease activity with changes in cholesterol over time. Decreases in the 28‐joint Disease Activity Score, the C‐reactive protein level, or the erythrocyte sedimentation rate were associated with increases in levels of HDL cholesterol, LDL cholesterol, and total cholesterol in all treatment groups ( P < 0.001–0.035). Triple therapy was strongly associated with higher levels of HDL cholesterol, lower levels of LDL cholesterol, and higher ratios of total cholesterol:HDL cholesterol ( P < 0.001 for all) compared to MTX monotherapy or MTX plus etanercept therapy over the 2‐year followup. Conclusion: Decreases in RA disease activity over long‐term followup were associated with increases in cholesterol levels in patients with early RA treated with either biologic or nonbiologic therapies. The use of triple therapy during 2 years of followup was associated with higher HDL cholesterol levels, lower LDL cholesterol levels, and lower total cholesterol:HDL cholesterol ratios compared to those observed in patients who received MTX monotherapy or MTX plus etanercept combination therapy. Additional studies are needed to assess the effects of these cholesterol changes on CV events in patients with RA.